Understanding the shift from micro to macro-prudential thinking: A discursive network analysis - Matthias Thiemann; Mohamed Aldegwy; Edin Ibrocevic (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
While some economists argued for macro-prudential regulation pre-crisis, the macro-prudential approach and its emphasis on endogenously created systemic risk have only gained prominence post-crisis. Employing discourse and network analysis on samples of the most cited scholarly works on banking regulation as well as on systemic risk (60 sources each) from 1985 to 2014, we analyze the shift from micro to macro-prudential thinking in the shift to the post crisis period. Our analysis demonstrates that the predominance of formalism, particularly, partial equilibrium analysis along with the exclusion of historical and practitioners' styles of reasoning from banking regulatory studies impeded economists from engaging seriously with the endogenous sources of systemic risk prior to the crisis. Post-crisis, these topics became important in this discourse, but the epistemological failures of banking regulatory studies precrisis were not sufficiently recognized. Recent attempts to conceptualize and price systemic risk as a negative externality point to the persistence of formalism and equilibrium thinking, with its attending dangers of incremental innovation due to epistemological barriers constrains theoretical progress, by excluding observed phenomena, which cannot yet be accommodated in mathematical models.
urn:nbn:de:hebis:30:3-400683
Keywords: B40; B41; G18; G28; 330; Banking Regulation; Systemic Risk; Formalism; Equilibrium Thinking; Discourse and Citation Network Analysis